Are emotional people more happy? A moderated mediation approach. (4th April 2023) - Lather, Anu Singh; Kaur, Simran
The current study empirically investigated a moderated mediated model of the psychological need for relatedness with the employees' happiness level. This study examined the current gaps in literature and provided an empirical examination of relationships between psychological need for relatedness, emotional intelligence and employees' happiness level. A total of 195 responses were recorded to undertake the current study. Structural equation modelling approach along with Hayes' process macro was used to test the hypotheses. The findings showed that the need of relatedness along with the emotional intelligence enhanced the happiness level of employees. The mediation effects of emotional intelligence varied between male and female employees. This study applies self-determination theory to link psychological need for relatedness with employees' happiness level. This research is an endeavour to comprehend self-determination theory in service sector. The current study is based on empirical study, but a mixed methodology approach may provide a greater degree of understanding in this crucial field of research in future. The effect of various socio-demographic factors like age, gender, education, number of years serving the same organisation, etc., can also be analysed in future studies.